THE IMPORTANCE OF CO2 LASER IN DERMATOLOGY - Kholmatov Murodjon Sobirovich; Sharipov Alisher Urmanovich; Kamalov Azizbek Ruzalievich; Begmatov Islombek G'anievich (Web of Journals Publishing, 2025)
This article explores the critical role of CO2 lasers in dermatology, examining their mechanisms, applications, and clinical outcomes. A comprehensive literature analysis highlights the advancements in laser technology, while the discussion provides insights into their future potential in skin treatments.
Keywords: CO2 laser, dermatology, skin resurfacing, scar treatment, skin rejuvenation, laser therapy, clinical outcomes, minimally invasive.